Three new species of Axinulus (Bivalvia: Thyasiridae) from the Japan and Kuril-Kamchatka trenches and abyssal zone of the northern Pacific Ocean - Gennady M. Kamenev (PeerJ, 2023)
The Thyasiridae is one of the most species-rich families of bivalves in the deep-sea areas of the northern Pacific Ocean. Many thyasirid species form abundant populations in these regions and play an important role in the functioning of deep-sea benthic communities. However, most of these deep-sea thyasirid species have not been identified and many of them are new to science. Based on the material of bivalves collected by eight deep-sea expeditions in the northern Pacific Ocean during the period from 1954 to 2016, three new species of the genus Axinulus (Axinulus krylovae sp. nov., A. alatus sp. nov., and A. cristatus sp. nov.) are described from the Kuril-Kamchatka and Japan trenches, the Bering Sea, and other deep-water regions of the northern Pacific Ocean (3,200–9,583 m depth). The new species are distinguished due to a unique and complex sculpture of the prodissoconch, including tubercles and numerous thin folds of varying length and shape, as well as due to a thickening of the shell in the adductor scar areas, thus rendering the scars raised above the inner surface of the shell. Comparisons with all species of the genus Axinulus are provided.